1997
DOI: 10.1007/s002619900140
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathological focal enhancements on spiral CT hepatic angiography

Abstract: In nearly half of patients, spiral CTA shows various shapes of small nonpathological focal enhancements more frequently in the liver edge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
1
10
2
Order By: Relevance
“…The frequency of these nonpathological enhancements seen on HAP or CTA images was significantly higher than that noted in a previous report [41], which is probably due to higher spatial resolution of current CT technology, less partial volume-averaging effects when employing thinner slices, and less respiratory misregistration when using the helical CT scanner [38].…”
Section: Portal Veincontrasting
confidence: 46%
See 2 more Smart Citations
“…The frequency of these nonpathological enhancements seen on HAP or CTA images was significantly higher than that noted in a previous report [41], which is probably due to higher spatial resolution of current CT technology, less partial volume-averaging effects when employing thinner slices, and less respiratory misregistration when using the helical CT scanner [38].…”
Section: Portal Veincontrasting
confidence: 46%
“…This fact explains the observation that these regions match perfectly with the focal nontumoral perfusion defects detected with helical CT during arterial portography (CTAP) [28,30]. The liver parenchyma with aberrant gastric or cystic venous drainage is shown as a hyperattenuating lesion on CTA [38]. On scans of dual-phase helical CT, HAP images may show the involved areas to be hyperattenuating relative to normal liver parenchyma and PVP images show homogeneous enhancement [8].…”
Section: Portal Veinmentioning
confidence: 73%
See 1 more Smart Citation
“…Causes for the false-positive diagnosis of hepatic tumor based on CTHA and CTAP studies reported thus far include cystic venous drainage [1,8,10], aberrant gastric venous drainage [7], anatomically normal (inferior vein of Sappey) or abnormal portosystemic venous communication [11][12][13][14][15], small arterioportal venous shunts [15], compensatory increase and/or congestion in hepatic arterial flow due to portal or hepatic venous flow stoppage [1,16], and other miscellaneous factors. Findings that increase the suspicion for a pseudolesion include atypical Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5), or localization in sites with a high propensity for pseudolesions. Combining CTHA with CTAP generally helps to increase the specificity that would be obtained with CTAP alone [10,13,[17][18][19][20]. Kanematsu et al reported nonpathological focal enhancement on helical CTHA in 31 patients suspected of having liver tumors and analyzed the frequency, size, shape, and relationship with findings on CTAP [10].…”
Section: Figmentioning
confidence: 98%